2016
DOI: 10.1186/s13071-016-1746-4
|View full text |Cite
|
Sign up to set email alerts
|

The geographical distribution and prevalence of Echinococcus multilocularis in animals in the European Union and adjacent countries: a systematic review and meta-analysis

Abstract: BackgroundThis study aimed to provide a systematic review on the geographical distribution of Echinococcus multilocularis in definitive and intermediate hosts in the European Union (EU) and adjacent countries (AC). The relative importance of the different host species in the life-cycle of this parasite was highlighted and gaps in our knowledge regarding these hosts were identified.MethodsSix databases were searched for primary research studies published from 1900 to 2015. From a total of 2,805 identified scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 143 publications
4
165
0
12
Order By: Relevance
“…On the other hand, in Lithuania, bordering on the investigated area, the prevalence was very high (58.7%) (7), similarly as in other Baltic countries (1,18). It is regarded that in the same area, generally, the prevalence of this tapeworm in raccoon dogs was even several times lower than in red foxes (21). Therefore, the lack of E. multilocularis positive raccoon dogs in the Augustów Primeval Forest along with its relatively low prevalence in red foxes was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Lithuania, bordering on the investigated area, the prevalence was very high (58.7%) (7), similarly as in other Baltic countries (1,18). It is regarded that in the same area, generally, the prevalence of this tapeworm in raccoon dogs was even several times lower than in red foxes (21). Therefore, the lack of E. multilocularis positive raccoon dogs in the Augustów Primeval Forest along with its relatively low prevalence in red foxes was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identification performed in other cases of Swedish cats have shown that these oocysts belong to Toxoplasma gondii (SVA, unpublished results). Regarding taeniid eggs, different species are morphologically indistinguishable and since no polymerase chain reaction (PCR) was performed, species could not be determined and it cannot be excluded that some of them were eggs of Echinococcus multilocularis , even if it has been shown that are only rarely infected by this parasite and moreover in Sweden E. multilocularis eggs or DNA have only been detected in faeces from foxes [18, 19]. Based on previous data from necropsy studies performed on Swedish cats the likelihood that these eggs belong to T. taeniaeformis is very high.…”
Section: Methodsmentioning
confidence: 99%
“…It is thus plausible that E. multilocularis is being transmitted in some portion via red foxes also in north-eastern Romania. The Moldova Republic neighboring eastward is classifi ed as a country with uncertain endemicity status (Oksanen et al, 2016;EFSA, 2016), having a single record of E. multilocularis from house mouse in 1961 (Abuladze, 1964;Bessonov, 2002). Nevertheless, the country is believed to be endemic for the parasite over at least part of its territory, with 1 estimated annual number of human cases according to Torgerson et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest records, the known range of E. multilocularis has markedly extended across Europe and it is assumed to be currently distributed over the most of its territory. For countries of central-eastern Europe, evidence supports northward and southeastern expansions from a core endemic area in south-central Europe as documented by fi ndings from Poland, Baltic countries, Slovakia, Hungary, Romania (summarized in Davidson et al, 2012 andOksanen et al, 2016). Prevalence trends of AE in humans appear to follow the surge in parasite abundance in wildlife coinciding with dramatic increases of fox population that began since 1990´s (Mackenstedt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%